Konsep Nilai Ta’dzhim al-Ilmi wa Ahlihi Dalam Kitab Ta’lim Al Muta’alim (Implementasi pada Pembelajaran Bahasa Arab) - Ramanali, heriansah (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2024)
The concept of ta'zhim al-Ilmi wa Ahlihi is a fundamental thing to emphasize to students from an early age. Because with this concept students will have manners and respect, especially towards their teachers. This value is very important to counter foreign cultures which tend to have values ​​that are contradictory to Islamic values. Darul Fattah Qur'an Middle School (SMPQ-DF) is one of the schools that implements Arabic in the school environment quite well.. Having good character and manners as well as a conducive Arabic language environment is an attraction for conducting research in the South Lampung SMPQ-DF environment.This research is a type of qualitative research, data was collected by interviews, observation and documentation. The concept of ta'dzhim in the book ta'lim al-muta'allim includes ta'dzhim towards knowledge and towards scientific experts. Ta'dzhim towards knowledge is by glorifying the book and practicing and glorifying knowledge. Meanwhile, ta'dzhim towards scientific experts or teachers is to honor the teacher and respect the teacher's children, family and relatives. So the concept of the value of ta'dzhim that Al-Zarnuji means is respect for knowledge and teachers which is manifested in the daily behavior of students of knowledge. The implementation of the value of ta'dzhim in learning Arabic at SMPQ-DF Lampung Selatan is going well, this is reflected in the pre learning activities, learning process activities and post-learning activities that prioritize the value of ta'dzhim. Keywords: Arabic learning, ta'dzhim concept